2010
DOI: 10.1590/s1516-18462010005000100
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de supressão das emissões otoacústicas evocadas por estímulo transiente em lactentes de risco para perda auditiva nascidos pré-termo

Abstract: OBJETIVO: verificar a ocorrência e a magnitude do efeito de supressão das emissões otoacústicas evocadas por estímulo transiente, em lactentes nascidos pré-termo, com indicadores de risco para perda auditiva. MÉTODOS: a supressão das emissões otoacústicas evocadas por estímulo transiente foi realizada em 15 lactentes nascidos pré-termo. O equipamento utilizado foi o ILO USB II V6 Clinical OAE, de marca Ododynamics. O estímulo clique linear foi apresentado a 60 dB pe NPS (± 5) e o ruído contralateral (ruído bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…Comparing the mean postconceptional ages of G1 (45.8 weeks) and of G2 (42.9 weeks), it is observed that, in both groups, process of maturity is not modified from the 38 th week onwards 13 . When comparing the means of the amplitudes of the TEOAE in the right ear, between G1, G2A and G2B, there was a statistically significant difference in between G2B and G1 (Table 5).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparing the mean postconceptional ages of G1 (45.8 weeks) and of G2 (42.9 weeks), it is observed that, in both groups, process of maturity is not modified from the 38 th week onwards 13 . When comparing the means of the amplitudes of the TEOAE in the right ear, between G1, G2A and G2B, there was a statistically significant difference in between G2B and G1 (Table 5).…”
Section: Discussionmentioning
confidence: 92%
“…It has also been observed that the amplitudes of OAE in children are much greater than in adults 13 . However, another study with newborns before and after the 38 week postconceptional period showed an increase in the TEOAE after 38 weeks, indicating that the maturation process of the active mechanisms of the cochlea and the properties of the middle ear occurs after the 38 th week…”
Section: This Study Was Submitted To the Research Ethicsmentioning
confidence: 97%
“…Legend: DP = standard deviation; SR = without contralateral noise; CR = with contralateral noise; OD = right ear; OE = left ear asymmetric activity between the ears and, consequently, a magnitude of greater suppression on the right ear 3,11 . Such findings provide new arguments in favor of the peripheral auditory lateralization, especially in regard to the medial efferent system.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors verified the occurrence and the magnitude of the suppression effect of otoacoustic emissions by transient stimulus, in preterm infants, with risk factors for hearing loss and observed greater responses in the right ear 11 . Values greater of the amplitude suppression of transient otoacoustic emissions in the right ear using a noise in the ear contralateral and changes in amplitude of these emissions during tasks of auditory and visual attention indicate that the medial olivocochlear tract may be involved in maintaining this asymmetric peripheral standard and through him, the cortex can modulate cochlear function 8,9,12 .…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation